A critical review on the progress of emerging active and substrate materials for organic solar cells and device level fabrication techniques by solution process method - Majhi, Jagannath; Ghosh, Samaresh; Priya, Kumari; Sharma, Sonal; Bandyopadhyay, Anasuya (Next materials, 2025)
Energy crisis is one of the major issues at present at the global level. Harvesting of solar energy by photovoltaic cells has the potential to compensate for this large energy requirement. As commercially available silicon-based solar cells have many disadvantages like high processing cost, rigidity, etc., organic solar cells are currently the subject of extensive research as an alternative to replace them. Because of the development of highly efficient donor-acceptor material, this type of solar cell has achieved a remarkable power conversion efficiency (PCE) above 20 %. Along with that side chain engineering of the active large and efficient optimization of nanoscale morphology of the active material also helps to enhance the performance of the solar cells. Generally, photovoltaic cells are composed of a cathode, anode, active layer made with donor and acceptor materials, and transparent substrate material. The active layer plays a pivotal role in the performance of the device and it mainly determines how effectively organic solar cells can convert solar energy to electrical energy. Furthermore, the substrate is also a crucial component since all other layers are deposited on it, allowing sunlight to pass through while serving as a barrier to shield the solar cells. In this review article, we have specifically concentrated on the development of active layers, substrate material, and the effects of nano-scale morphology. We also surveyed the different fabrication techniques by solution process methods for fabricating organic solar cells. [Display omitted] •Organic solar cells are cheaper, less space-intensive, and require low maintenance.•The principle of photocurrent generation in organic solar cells has been discussed.•Classifications based on the device architecture and active layer are surveyed.•Emerging active and substrate materials and morphological effects are compiled.•Commonly used solution-processed fabrication techniques are summarized.